Enhanced Host-Parasite Resistance Based on Down-Regulation of Phelipanche aegyptiaca Target Genes Is Likely by Mobile Small RNA - Dubey, Neeraj K.; Eizenberg, Hanan; Leibman, Diana; Wolf, Dalia; Edelstein, Menahem; Abu-Nassar, Jackline; Marzouk, Sally; Gal-On, Amit; Aly, Radi (Frontiers in Plant Science, 2017)
RNA silencing refers to diverse mechanisms that control gene expression at transcriptional and post-transcriptional levels which can also be used in parasitic pathogens of plants that Broomrapes (Orobanche/Phelipanche spp.) are holoparasitic plants that subsist on the roots of a variety of agricultural crops and cause severe negative effects on the yield and yield quality of those crops. Effective methods for controlling parasitic weeds are scarce, with only a few known cases of genetic resistance. In the current study, we suggest an improved strategy for the control of parasitic weeds based on trans-specific gene-silencing of three parasite genes at once. We used two strategies to express dsRNA containing selected sequences of three Phelipanche aegyptiaca genes PaACS, PaM6PR, and PaPrx1 (pma): transient expression using Tobacco rattle virus (TRV:pma) as a virus-induced gene-silencing vector and stable expression in transgenic tomato Solanum lycopersicum (Mill.) plants harboring a hairpin construct (pBINPLUS35:pma). siRNA-mediated transgene-silencing (20–24 nt) was detected in the host plants. Our results demonstrate that the quantities of PaACS and PaM6PR transcripts from P. aegyptiaca tubercles grown on transgenic tomato or on TRV-infected Nicotiana benthamiana plants were significantly reduced. However, only partial reductions in the quantity of PaPrx1 transcripts were observed in the parasite tubercles grown on tomato and on N. benthamiana plants. Concomitant with the suppression of the target genes, there were significant decreases in the number and weight of the parasite tubercles that grew on the host plants, in both the transient and the stable experimental systems. The results of the work carried out using both strategies point to the movement of mobile exogenous siRNA from the host to the parasite, leading to the impaired expression of essential parasite target genes.